2010
DOI: 10.1002/mrc.2679
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of vicinal proton–proton coupling constants of heteroaromatic molecules in terms of topological electron density descriptors

Abstract: The indirect vicinal proton-proton coupling constants for pyrrole, furan, thiophene and 15 related heteroaromatic compounds were calculated using the Khon-Sham approximation. An analysis of the four Ramsey contributions to the coupling constants was carried out showing that the Fermi contact term is always positive and dominant, although the remaining contributions have a nonnegligible net negative contribution. The trends observed for the proton-proton coupling constants were rationalized in terms of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, the proton-proton coupling constants and their 4 Ramsey contributions were computed for heteroaromatic compounds such as pyrrole, furan, thiophene, and other 5-membered ring molecules. [89] It was found that although the contact term is dominant in most cases, there are molecules where the other components are also important, as can be seen in Figure 15. The trends observed for the coupling constants were rationalized in terms of electron density descriptors using multivariate correlations of the form…”
Section: Indirect Coupling Constantsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the proton-proton coupling constants and their 4 Ramsey contributions were computed for heteroaromatic compounds such as pyrrole, furan, thiophene, and other 5-membered ring molecules. [89] It was found that although the contact term is dominant in most cases, there are molecules where the other components are also important, as can be seen in Figure 15. The trends observed for the coupling constants were rationalized in terms of electron density descriptors using multivariate correlations of the form…”
Section: Indirect Coupling Constantsmentioning
confidence: 92%
“…This approach has been extended to a wide variety of systems. For example, the proton–proton coupling constants and their 4 Ramsey contributions were computed for heteroaromatic compounds such as pyrrole, furan, thiophene, and other 5‐membered ring molecules . It was found that although the contact term is dominant in most cases, there are molecules where the other components are also important, as can be seen in Figure .…”
Section: Applications Of Qtaimmentioning
confidence: 99%
“…Likewise, reaction of 2 with thiophene 5g in the presence of triflic acid afforded the 2- and 3-substituted products, 4g and 4g ′, in a 1.2:1 ratio in yields of 26 and 21%, respectively. The assignment was made by comparing the coupling constants for the three aromatic protons and by analogy to literature data …”
mentioning
confidence: 99%